Fabrication of a low-cost functionalized poly(vinylidene fluoride) nanohybrid membrane for superior fuel cells. Issue 5 (5th April 2019) - Prakash, Om; Jana, Karun Kumar; Manohar, Murli; Shahi, Vinod K.; Khan, Saif A.; Avasthi, Devesh; Maiti, Pralay
Abstract : Advanced membrane was designed by creating nanochannels using swift heavy ions from an accelerator. Fuel cell was fabricated using the novel membrane and demonstrated high power density as compared to standard Nafion. Abstract : Nanochannels were created in poly(vinylidene fluoride) and its nanohybrid films by bombarding with high-energy swift heavy ions. The nanochannel dimensions of the membranes varied from 80 to 100 nm using 5 × 10 7 ion fluence of SHIs. The walls of the nanochannels were grafted with the monomer 3-hexylthiophene using the free radicals generated by the swift heavy ions, which was followed by their sulphonation for better ion conduction. Organically modified nanoclay enhanced the electroactive β-phase in the polymer and its extent increased after irradiation, grafting and sulphonation, resulting in a better material for different electroactive applications. The semiconducting current–voltage characteristics of the functionalized nanochannels were studied through a parameter analyzer of the bulk film against the insulating behavior of the neat polymer. The current–voltage characteristic of the membrane exhibited strong dependency on functionalization and showed superior conduction in the functionalized nanohybrid membrane. The proton conductivity of the functionalized nanohybrid was 4.59 × 10 −2 S cm −1 at 30 °C, while methanol permeability was drastically reduced as compared to that of standard Nafion 117; this indicated the higher values of the selectivity parameter, which is a key feature of the better performance of the fuel cell membrane: 1.02 × 10 5 S cm −3 s as opposed to the value of 0.73 × 10 5 S cm −3 s for Nafion 117. The membrane electrode assembly studies of the functionalized nanohybrid showed 0.76 V open circuit voltage, leading to power density of 92 mW cm −2 and current density of 252 mA cm −2, which were significantly higher than those of the functionalized pure polymer and standard Nafion 117 membrane, indicating its good potential for applications in fuel cells.